Use of Web 2.0 Technology in English Language Teaching (ELT) in Remote Indonesian Universities: Opportunities and Challenges - Sutaryo, Nurprihatina Hasan; Saiful Latif (International Journal of Advanced Science and Technology, 2020)
This research aims at 1). Exploring lecturers’ and students’ experiences in using Web 2.0 tools in English Language Teaching (ELT) in remote Indonesian universities; 2). Identifying types of Web 2.0 tools used by lecturers in ELT; and 3). Identifying obstacles faced by lecturers and students in integrating Web 2.0 tools in ELT. A total of 15 lecturers and 92 students from six Study Programs majoring in English Language Education or English Literature in five universities, both public and private, in North Maluku province, Indonesia voluntarily participated in this study. Data collected through interviews were analyzed thematically. The findings show that students become more enthusiastic and motivated to learn English through the integration of web 2.0 tools in ELT. Despite a very few lecturers use Web 2.0 tools, such as Google Classroom and Edmodo, they provide more benefits for both lecturers and students than their shortcomings. The benefits include allowing both lecturers and students to upload learning materials and assignments respectively with various file formats, students’ grade transparency, allowing private communication, simple menus, building students’ awareness to submit their assignments on time, and as reminders for lecturers in regard to learning materials. A primary obstacle is related to the inadequate internet networks provided by universities and consequently, both lecturers and students often have to afford internet data packages to allow their web 2.0 tools running.